THE MEDIATING ROLE OF EMPLOYEE CREATIVITY IN THE EFFECT OF INTRINSIC MOTIVATION, COWORKER SUPPORT, AND SUPERVISOR SUPPORT ON EMPLOYEE ENGAGEMENT - Royyan Fakhrudin Rifai; Susanto Tirtoprojo (Proceeding International Seminar of Islamic Studies, 2023)
Employee engagement is one of many aspects that influence organizational performance, and sometimes within an organization there are still problems related to employee engagement. The purpose of this research is to understand the effect of intrinsic motivation, supervisor support, and co-worker support to employee engagement mediated by employee creativity. Data were collected from 124 full-time workers in the industrial sector. This study used cross sectional method and used SmartPLS software. The results of the study have shown that employee creativity could mediate the relation of intrinsic motivation and co-worker support to employee engagement, but employee creativity could not mediate the relationship of supervisor support to employee engagement. By understanding the results of this research, hopefully the executive of industrial sector can understand variables that effect employee engagement and adjust the internal activity of company in order to gain high employee engagement.